101 A 16 Year Review of Deaths Due to Cardiovascular Disease in the United Kingdom Armed Forces. (31st May 2014) - Cox, Andrew; Pratt, Gavin; Byrne, Edd; Baird, Lisa; Harrison, Kate; Wilson, Duncan; Sharma, Sanjay
Abstract : Background: It is known that approximately 10% of deaths in the UK Armed Forces result from cardiovascular disease.Characterisation of the underlying diagnoses has never been performed and doing so may present opportunities for preventative intervention. Methods: All military deaths are reported to Defence Statistics.They are cross referenced with death certificate and autopsy information and categorised using the WHO ICD-10 system.Deaths were recorded from April 1995 to March 2011 inclusive with crude rates recorded per 100, 000 Service years. Results: 253 cardiovascular deaths were recorded over 2, 765, 410 Service years (rate 9.15 per 100, 000).Males comprised 91.3% of the population at risk but 96.0% of deaths.In those aged <35 years 90 deaths (rate 3.25 per 100, 000) were recorded with 163 deaths in those >35 years (rate 5.89 per 100, 000).The most common cause of death was secondary to atheromatous coronary artery disease (107 deaths, rate 3.87 per 100, 000). More than a quarter were due to congenital and inherited diseases (33 deaths, rate 1.19 per 100, 000) or Sudden Arrhythmic Death Syndrome (SADS) (36 deaths, rate 1.30 per 100, 000); a syndrome often due to various inherited conditions. Other important causes were strokes, aortic dissection, myocarditis, vascular disease and pulmonary emboli. Discussion: Cardiovascular disease from ischaemic heart disease and inherited conditions cause a significant mortality burden.Policy should be directed at minimising the development of ischaemic heart disease.As inherited cardiac disease deaths usually occur in individuals asymptomatic prior to death early disease identification through screening might prevent many of these deaths.